2002
DOI: 10.1046/j.1523-1755.2002.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Sevelamer attenuates the progression of coronary and aortic calcification in hemodialysis patients

Abstract: Compared with calcium-based phosphate binders, sevelamer is less likely to cause hypercalcemia, low levels of PTH, and progressive coronary and aortic calcification in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
1,117
16
35

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,344 publications
(1,218 citation statements)
references
References 33 publications
50
1,117
16
35
Order By: Relevance
“…The use of CART also identified the relationship between serum calcium concentrations and defective mineralization. Indeed, low serum calcium levels and high serum PTH values were the strongest predictors of mineralization defect in patients with bone turnover within the normal range, a finding that should be taken into consideration in view of the availability of therapeutic agents, such as calcium-free phosphate binders (10,27) and calcimimetic agents (28), which maintain serum calcium levels within the lower normal range. None of the patients included in this analysis received any of these agents before bone biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CART also identified the relationship between serum calcium concentrations and defective mineralization. Indeed, low serum calcium levels and high serum PTH values were the strongest predictors of mineralization defect in patients with bone turnover within the normal range, a finding that should be taken into consideration in view of the availability of therapeutic agents, such as calcium-free phosphate binders (10,27) and calcimimetic agents (28), which maintain serum calcium levels within the lower normal range. None of the patients included in this analysis received any of these agents before bone biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adverse CVD events in CKD are often due to heart failure, which may be related to higher serum phosphorus, at least in part because of its effect to promote cardiac valvular and muscle calcification (7,15,23,24). Clinical trials of phosphate reduction have been limited by selection of only participants with ESRD and insufficient clinical outcomes data to draw firm conclusions (25,26). Observational human data combined with experimental studies make a case for testing effects of treatments that reduce phosphate on CVD outcomes in patients who are in earlier stages of CKD or perhaps even in those who do not have CKD but have CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Chertow et al (23) and Asmus et al (24) demonstrated that sevelamer hydrochloride treatment compared with calcium carbonate resulted in a decreased rate of increase in vascular calcium in dialysis patients. Sevelamer therapy in humans often is associated with a reduction in serum cholesterol (23,25) as observed in the studies reported here. Phan et al (26) demonstrated that sevelamer hydrochloride decreased the calcification of atherosclerotic plaques during an 8-wk prevention trial in apolipoprotein E-deficient mice that were made uremic by the procedure used in our study.…”
Section: Discussionmentioning
confidence: 99%